Evaluation of genotoxic and antigenotoxic effects of boron by the somatic mutation and recombination test (SMART) on Drosophila. (1st October 2016) - Sarıkaya, Rabia; Erciyas, Kamile; Kara, Muhammed Isa; Sezer, Ufuk; Erciyas, Ali Fuat; Ay, Sinan
Abstract: Objective : In this study, different concentrations of boron have been evaluated for genotoxic and antigenotoxic properties by using the somatic mutation and recombination test (SMART) on Drosophila melanogaster. Study Design : The treatment concentrations were chosen to a pretest. Third-instar larvae trans-heterozygous for two genetic markers, multiple wing hair ( mwh ) and flare ( flr 3), were treated at different concentrations (0.1, 5, 10, 20, and 40 mg/mL) of boron. In addition to investigating antigenotoxic effects, the same boron concentrations were co-administered with 0.1 mM Ethyl Methane Sulfonate (EMS). Distilled water was used as a negative control; 0.1 mM of EMS was used as a positive control. For the chronic feeding study, small plastic vials were prepared with 1.5 g of dry Drosophila Instant Medium and 5 mL of the respective test solution. Hundreds of trans-heterozygous larvae were embedded into this medium. Feeding ended with pupation of the surviving larvae. After metamorphosis, all surviving flies were collected and stored in a 70% ethanol solution. Preparation and microscopic analyses of wing were made after the treatment. Then the observed mutations were classified according to size and type of mutation per wing. Results : Results indicated that there is no significant genotoxic effect with all of the boron concentrations. In addition, the antigenotoxic activities of boron against EMS were tested. Results indicated that all boron concentrations (0.1, 5, 10, 20 and 40 mg/mL) were able to abolish the genotoxic effects induced by the EMS. Conclusion : It is suggested that the observed effects can be linked to the antioxidant properties of boron. Moreover, these in vivo results will contribute to the antigenotoxicity database of boron.